CORRELATION BETWEEN TOTAL LIPIDS, LINOLENIC ACID AND MEMBRANE INJURY UNDER PEG-INDUCED DEHYDRATION IN LEAVES OF VIGNA GENOTYPES DIFFERING IN DROUGHT RESISTANCE - Scotti-Campos, Paula; Pham-Thi, Anh-Thu (Emirates Journal of Food and Agriculture, 2017)
Membrane lipids contain trienoic fatty acids which enhance fluidity, an essential feature for optimal membrane performance. However highly unsaturated molecules are prone to lipoperoxidation processes. In V. unguiculata, linolenic acid (C18:3) accounts for more than 90% of the total fatty acids of galactolipids. High C18:3 contents causes galactolipids molecules, especially monogalactosyl-diacylglycerol (MGDG), to become more susceptible to drought-induced peroxidative or enzymatic degradation. In this work 8 Vigna genotypes differing in drought resistance in the field were compared to search for an eventual correlation between genotypes ability to resist to water stress and some characteristics of their membrane lipids in well-watered plants. Plants were grown in a greenhouse with semi-controlled environmental conditions, and kept fully hydrated. Leaves were collected from one month old plants to perform electrolyte leakage test under PEG-induced dehydration and lipid analysis. Results showed that both a reduced amount of total lipids, which reflects a small amount of membranes, and a reduced amount of C18:3 in MGDG, which indicates a low membrane fluidity, were strongly correlated with a high membrane resistance to dehydration, and therefore seem to be useful screening tools for drought-tolerant genotypes. Taking into account what is known concerning drought resistance of the genotypes under study, it was also concluded that the degree of membrane resistance to osmotic stress could be extrapolated to drought resistance in the field.